Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Etos Kerja Karyawan - Syawali, Imam; Suriadi, Ahmad; Komalasari, Shanty (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2021)
This study aims to determine the effect of emotional intelligence and spiritual intelligence on the work ethic of employees in the South Kalimantan Provincial Health Office. This type of research is field research with a quantitative approach. The population in this study were employees at the South Kalimantan Provincial Health Office and 62 respondents were the respondents. Based on this research, the results obtained: 1) There is a significant influence between emotional intelligence on the work ethic of employees in the South Kalimantan Provincial Health Office, with a significance level of 0,000 (p value <0,05) and an effective contribution of 40,4%. 2) There is a significant influence between spiritual intelligence on the work ethic of employees in the South Kalimantan Provincial Health Office, with a significance level of 0,000 (p value <0,05) and an effective contribution of 59,4%. 3) There is a significant influence simultaneously or together between emotional intelligence and spiritual intelligence on the work ethic of employees in the office environment of the South Kalimantan Provincial Health Office, with a significance value or p value is 0,000 (p value <0,05), as well as the influence which were given simultaneously or together amounting to 59,5%.